Field Evidence of a Natural Capillary Barrier in a Gravel Alluvial Aquifer - Halihan, T. (2020)
Ozark streams commonly feature “composite” floodplains, in which the vadose zone consists of silt or silt loam soils (∼1 m thick) overlying gravel subsoil. Previous work has shown that preferential flow paths can exist within the gravel subsoil, which can conduct water and P at rates exceeding the sorption capacity of the gravel. At a site on Barren Fork Creek, a 1‐ by 1‐m infiltration plot was constructed and an infiltration experiment was performed using sequentially introduced solutes including P (the constituent of regulatory interest), Rhodamine‐WT (Rh‐WT, a visual tracer), and Cl− (an electrical tracer). The solute transport was measured with monitoring wells (MWs) placed 1 m from the plot boundary and 5 m down the groundwater flow gradient using an electrical resistivity imaging (ERI) array. The ERI method utilized differences between a pre‐infiltration background image and subsequent temporal images taken during the test to quantify changes induced by the tracers. The infiltration test maintained a steady‐state flow rate of 4.5 L min−1 for 84.75 h. Electrical resistivity imaging data showed significant changes in resistivity induced by the tracers within the soil vadose zone under the plot but no similar changes within the gravel, indicating that the interface was acting as a capillary barrier. Electrical resistivity images 5 m away from the plot showed tracer breakthrough into the gravel in areas not sampled by the MWs. Solute detection was limited in MWs, indicating that MWs could not adequately monitor movement below the capillary barrier because it controlled migration of solute to the heterogeneous phreatic zone.